Analysis and Reconstruction Design of Laboratory Activities in Osmosis Materials - Tanfiziyah, Rifda Tanfiziyah; Supriatno, Bambang; Anggraeni, Sri (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Practicum and laboratory activities cannot be taken from biology learning. Activities require LaboratoryActivity Designs and Student Worksheets as instructions for their implementation. Based on the results ofa field study) that student worksheet measured in the field has several problems. Therefore, to overcomethis, an in-depth analysis and reconstruction of student worksheet is needed. This study aims to describethe results of the analysis, trials and reconstruction of student worksheet osmosis to meet the requirementsof the 2013 curriculum. The research method used is descriptive qualitative with a sample of 8 studentworksheet from the 2004 curriculum, school based curriculum and 2013 curriculum. The selected studentworksheet uses purposive sampling technique. The research instrument used was in the form of practicalanalysis, knowledge construction, and the relevance of the curriculum and content. Based on the results ofthe relevance analysis, most of the student worksheet are relevant to the curriculum. From the aspect ofknowledge construction, student worksheet cannot yet describe the development of student skills. Theresults of the reconstruction that have been made have been assessed by experts. The research method usedis descriptive qualitative with a sample of 8 student worksheet from the 2004 curriculum, school basedcurriculum and 2013 curriculum. Based on the results of the relevance analysis, most of the studentworksheet are relevant to the curriculum. From the aspect of knowledge construction, student worksheetcannot yet describe the development of student skills. The results of the reconstruction that have been madehave been assessed by experts.